Transmembrane Amyloid-Related Proteins in CSF as Potential Biomarkers for Alzheimer’s Disease - Lopez-Font, Inmaculada; Cuchillo-Ibañez, Inmaculada; Sogorb-Esteve, Aitana; García-Ayllón, María-Salud; Sáez-Valero, Javier (Frontiers in Neurology, 2015)
In the continuing search for new cerebrospinal fluid (CSF) biomarkers for Alzheimer’s disease (AD), reasonable candidates are the secretase enzymes involved in the processing of the amyloid precursor protein (APP), as well as the large proteolytic cleavage fragments sAPPα and sAPPβ. The enzymatic activities of some of these secretases, such as BACE1 and TACE, have been investigated as potential AD biomarkers, and it has been assumed that these activities present in human CSF result from the soluble truncated forms of the membrane-bound enzymes. However, we and others recently identified soluble forms of BACE1 and APP in CSF containing the intracellular domains, as well as the multi-pass transmembrane presenilin-1 (PS1) and other subunits of γ-secretase. We also review recent findings that suggest that most of these soluble transmembrane proteins could display self-association properties based on hydrophobic and/or ionic interactions leading to the formation of heteromeric complexes. The oligomerization state of these potential new biomarkers needs to be taken into consideration for assessing their real potential as CSF biomarkers for AD by adequate molecular tools.